Children and divorce: a study of Divorce Court supervision orders - Goode, Stephen (1988)
This research study was of the making and administration of Divorce Court Supervision Orders. Although established in England and Wales in 1958, there has been no detailed examination of supervision in domestic proceedings. In the 1979 period, when the population was obtained, 6,935 Divorce Court Supervision Orders were made. This figure has reduced to approximately 5,000 in 1985, with a total of 26,50C) ongoing orders. The population consisted of 121 children in 62 family units. Supervision could be undertaken by both probation officers or social workers. A review was undertaken of the original intentions of Divorce Court Supervision Orders as conceived by the Royal Commission on Marriage and Divorce 1951-55, and any subsequent amendments by legislation. Particular emphasis is also given to changing aspects of family law which might affect provision for children the history of social work to children in divorce proceedings was also examined. A detailed analysis was undertaken of descriptive material, on the place of children in divorce proceedings. This included research studies on the effects of divorce on children and any changes in the provision of services to parents and their children at the time of divorce proceedings. A full explanation is given of concepts such as conciliation. The original theoretical framework, placed the study of Divorce Court Supervision orders, in the wider context of the social policy of divorce proceedings. Reference is made to principles of family law and the possible relevance of a Juvenile Justice framework to the Divorce Court. In addition, Weber's concept of legitimacy was applied to the examination of Divorce Court Supervision Orders. The original research design, indicated the specific purposes of the research, which relate directly to the principles of a juvenile justice system. Details were given of the interview procedure, experience survey, identification of the validity and reliability considerations and the tests to be applied. The findings of the research are outlined in two chapters. They concentrate on the history of the families concerned, the nature of the divorce process and the details of Welfare Report recommendations. Due to the absence of any study of the process of supervision, as opposed to limited studies on the content of Divorce Court Welfare Reports, one chapter describes in some depth, the process of supervision. The analysis uses a combination of statistical tests and case examples. The use of case examples can illustrate most effectively the nature of the supervision provided. A section of the final empirical chapter addresses validity questions, by examination of what organisations a supervising officer had contact with during their involvement with a family, and the degree of continued jurisdiction of the Divorce Court over the supervision undertaken. A review of the main findings asks fundamental questions about the benevolence or control provided in domestic supervision. The final chapter places the present study, in the changing context of social work with children and their parents, involved in divorce proceedings. Child protectionism was identified as a fundamental principle, in spite of the last thirty years of reforms in family law. In addition, the final chapter questions the desirability of continued confusion over better services to divorcing parents and their children and child-protectionist based interventions by social work agencies. Parallels are drawn between the present study and other aspects of family law involving social work agencies. Throughout the research study, it was emphasised that the present research is exploratory and where appropriate, future areas of appropriate research were indicated.